Network Intrusion Detection System (NIDS) to Detect Botnet Attack using Rule-based and Signature-based Approach - NurQaseh Jeffy Irana Abdul Hakim; Isredza Rahmi Bt A Hamid (Applied Information Technology And Computer Science, 2026)
Botnets are a serious cybersecurity threat that allows Denial of Service (DOS) attacks and distribution of malwares. The existing Intrusion Detection System (IDS) is uncapable to identify the evolving and modern botnet threats. Therefore, a Network Intrusion Detection System (NIDS) is developed to detect the botnet attacks. This project aims to detect botnets using rule-based and signature-based detection by analysing the behaviour of the network traffic based on the predefined rules and signatures. We develop the NIDS using Agile methodology. The proposed NIDS can identify, alert and generate report for users that handles any sensitive information. This tool provides valuable insights to mitigate any future cyberattacks. Future plans for this tool are to update the tool according to evolving of the botnet attacks and implement real-time features.